Deposition of radiocesium on the river flood plains around Fukushima. (November 2016) - Saegusa, Hiromitsu; Ohyama, Takuya; Iijima, Kazuki; Onoe, Hironori; Takeuchi, Ryuji; Hagiwara, Hiroki
Abstract: The environment in the area around Fukushima Daiichi Nuclear Power Plant has been contaminated by widely deposited significant amount of radioactive materials, which were released to the atmosphere caused by the Fukushima Daiichi Nuclear Power Plant accident due to the Great East Japan Earthquake, which occurred on March 11, 2011. The radiocesium released in the accident mainly affects radiation dose in the environment. Decontamination work in the contaminated area except a mountain forests has been conducted to decrease the radiation dose. However, there are concerns that the redistribution of this radiation due to water discharge will occur due to the resulting transport of radiocesium. In particular, the deposition of soil particles containing radiocesium on the flood plains in the downstream areas of Fukushima's rivers can potentially increase the local radiation dose. Therefore, it is important to understand the influence of the deposition behavior of radiocesium on the radiation dose. Investigations of rivers have been performed to enhance the understanding of the mechanisms by which radiocesium is deposited on these flood plains. It was found that the spatial distribution of the radiocesium concentration on the flood plain along the river is heterogeneous with a dependence on the depositional condition and that the number of points with high air dose rates is limited. In detail, the radiocesium concentration and air dose rates in flood channels are higher than those at the edges of the river channels. Based on these heterogeneity and hydrological events, the deposition and transport mechanisms of the radiocesium due to water discharge at rivers were also interpreted, and a conceptual model was constructed. Highlights: The spatial distributions of the radiocesium concentrations on the flood plains are heterogeneous. The air dose rates in the flood channels are higher than those at the edges of the river channels. The number of points with high radiocesium concentrations in the flood channels is limited. Vegetation in the flood channels affects the radiocesium deposition process. A conceptual model of the deposition and transport of radiocesium was constructed.